Confucian business model canvas in the Asia Pacific: a Yin-Yang harmony cognition to value creation and innovation. Issue 3 (27th May 2021) - Chin, Tachia; Shi, Yi; Rowley, Chris; Meng, Jianwei
ABSTRACT: From an integrative view of paradox and culture, this research aims to elucidate the impact of cultural heterogeneity on the compositional structure of business models (BMs) in the Asia Pacific by focusing on the core BM content about the mechanisms of value creation and innovation. After a systematic review addressing the knowledge void, we refine the widely accepted, renowned model of a BM canvas to propose a new, indigenous Confucian BM canvas using the Yin-Yang harmony cognition as the underlying rationale for identifying the peculiar, innovative value-creating patterns of BMs in Confucian Asia. Our canvas encompasses three new building blocks: Social Legitimacy, Institutional Enabler, Institutional Disabler, that reflects the idiosyncratic Confucian cultural values and, thereby, can serve as a vital strategic map. Based on the insights distilled from this new canvas, we further suggest a novel 'networked synergistic mode of innovation for value creation' with an example of the electric motor industry in the Asia Pacific region. Theoretical, practical and policy implications are also discussed.